Nonoperative Management for T2 Low Rectal Cancer: A Western Approach - Fernandez, Laura Melina; São Julião, Guilherme Pagin; Vailati, Bruna Borba; Habr-Gama, Angelita; Perez, Rodrigo Oliva (Clinics in Colon and Rectal Surgery, 2020)
The possibility of organ preservation in early rectal cancer has gained popularity during recent years. Patients with early tumor stage and low risk for local recurrence do not usually require neoadjuvant chemoradiation for oncological reasons. However, these patients may be considered for chemoradiation exclusively for the purpose of achieving a complete clinical response and avoid total mesorectal excision. In addition, cT2 tumors may be more likely to develop complete response to neoadjuvant therapy and may constitute ideal candidates for organ-preserving strategies. In the setting where the use of chemoradiation is exclusively used to avoid major surgery, one should consider maximizing tumor response. In this article, we will focus on the rationale, indications, and outcomes of patients with early rectal cancer being treated by neoadjuvant chemoradiation to achieve organ preservation by avoiding total mesorectal excision.
Keywords: rectal cancer; watch and wait; early tumor